The Effectiveness of Animation Movie Through Retelling Technique to Improve The Students’ Speaking Ability - Irmayani, Irmayani (JLE: Journal of Literate of English Education Study Program, 2020)
This research aimed to find out the effectiveness of the use of animation movie through retelling technique to improve the students’ speaking ability of the eleventh years’ students of SMK Teknologi Somba Opu, Gowa. This research is a quasi experimental research and it employed a cluster random sampling technique. The researcher randomly selected two classes from four classes of the eleventh years based on their similarity in their speaking ability. Group A was as experimental group and group B became control group. The data were collected by using test. The result of data analysis indicated that the learning outcomes on speaking of the eleventh years’ students of SMK Teknologi Somba Opu taught by using animation movie through retelling technique was significantly increased after the treatment. The use of animation movie through retelling technique was effective in improving speaking ability with achievement of the students was better than conventional activity as indicated by the t-test value 13.804 and the p-value (2-tailed) .000 which was not greater than .05 level of significance.